2012
DOI: 10.1519/jsc.0b013e31823f8c06
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics and Physiological Attributes of Female Volleyball Players—The Need for Individual Data

Abstract: The purpose of this study was twofold: (a) to profile physical characteristics and physiological attributes of adolescent and adult Greek female volleyball players (n = 61) who were members of the A (the best league for female volleyball players) and B (the second-best league for female volleyball players) Series clubs in Greece and (b) to examine the intraindividual variability among these players in all physical and physiological measurements that were undertaken in the study. The participants were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 13 publications
(9 reference statements)
5
37
2
2
Order By: Relevance
“…spiking and blocking), volleyball players need to possess adequate cardiorespiratory power in order to cope with fatigue during match-play and training. This is supported by relevant research which has revealed high levels of cardiorespiratory power in adolescent and adult volleyball players [21,22,24] and by the findings of the present study. Therefore, achieving or maintaining an adequate level of cardiorespiratory power should be a concern of those involved in the training process.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…spiking and blocking), volleyball players need to possess adequate cardiorespiratory power in order to cope with fatigue during match-play and training. This is supported by relevant research which has revealed high levels of cardiorespiratory power in adolescent and adult volleyball players [21,22,24] and by the findings of the present study. Therefore, achieving or maintaining an adequate level of cardiorespiratory power should be a concern of those involved in the training process.…”
Section: Discussionsupporting
confidence: 90%
“…The participants in the present study had analogous anthropometric characteristics and body composition with other samples of Greek volleyball players [21,22]. Compared with 15.2-year-old volleyball players [22], the participants weighed less and were shorter, and had lower bMI and bF.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, in a recent study on female volleyball players (Nikolaidis et al, 2012), it was observed that large individual variability existed in most of the physical characteristics (e.g., body mass and height) and physiological attributes (e.g., aerobic capacity and anaerobic power) measured among the players, as well as that the intra-individual variability was observed in all age groups classified in this study (under 14, 14-18, and over 18 years of age). Intra-individual variability was also discussed in studies on elite pistol shooting performers (Ball et al, 2003) and elite golfers (Hassmen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Vertical countermovement jumps (VCMJs) are considered essential to success in volleyball, as they are used in both defensive (blocking) and offensive (attacking, passing, and serving) motions 1,2 VCMJs are performed frequently by volleyball players during training and competitions, and several studies have focused on how athletes can enable themselves to jump most effectively 3,4 Volleyball players must jump frequently in matches, making good jumping technique crucial. An analysis of two matches showed that the average player executed about 45 jumps and subsequent landings, and that the players' overall performance depended heavily on these actions 5 .…”
Section: Introductionmentioning
confidence: 99%